The Influence Of Literature Program On Science Literature Ability And Students' Interest In Science - Erna Yuliana; Ari Widodo; Ernawulan Syaodih (At-Tarbiyat, 2021)
Scientific literacy skills are very important for students to master in facing the challenges of life in the 21st century but based on the results of the 2018 PISA survey, Indonesian students are still in the bottom ten ranks. The low scientific literacy skills of Indonesians students is partly due to the use of science books at school which emphasizes the content dimension rather than the process and context dimensions as demanded by PISA, another factor is the low interest of students in science because of assumption that science is a difficult and boring subject. the purpose of this research is to improve scientific literacy skills and students interest in science by providing treatment in the form of reading popular science books every day. The research methode used is pre experimental research design with pretest and posttest design. The research sample was 45 students of class VI private elementary schools in the city of Bandung. Scientific literacy ability is measured using scientific literacy question in the competencies aspect with indicators referring to the 2018 PISA framework, while the measurement of students scientific interest is carried out using a Likert scale. Based on the result of data processing obtained an N-Gain value 0.52 for indicators explaining phenomena scientifically, an N-Gain value of 0.33 for indicators of evaluating and designing scientific enquiry and an N-Gain value of 0.64 for indicators of interpreting data and evidence scientifically. The results of students’ interest in science an N-Gain value of 0.31 for indicator of enjoyment of science, an N-Gain value of 0.26 for an indicator of interest in doing science activity, an N-Gain value of 0.49 for indicator of motivation to learn science and an N-Gain value of 0.34 for indicator of science related career so it can be concluded that literacy program is effective enough to improve scientific literacy skills and students’ interest in science.